(untitled) (Theatrum historiae, 2010)
The author defines the term “monetary calculation unit” in the economic context of the Early Modern Times and explains why, until the 16th century, this virtual concept was of exceptional importance. The specific use of monetary calculation units in the economic system of the time is explained taking as an example a unique preserved Hamburg exchange-rate table dating from 1595. The article then systematically summarises the development of monetary calculation units and their usage in Bohemia from the end of the 15th century to the beginning of the 17th century. The study also features examples of period summaries of the payment power of foreign coins dating from the 1570s and concise tabular summaries of Bohemian monetary calculation units and their equivalents in the physical coins minted between 1469 and 1619.